Prevalence of internal derangements of temporomandibular joint in patients with cleft-lip/palate - Grossmann, Eduardo (2018)
Aim: The aim of this study was to estimate the prevalence of internal derangements (ID) of temporomandibular joint (TMJ) in patients with cleft-lip/palate. Also, to evaluate the correlation of diagnosis between Research Diagnostic Criteria for temporomandibular disorders (RDC/TMD) clinical examination and Magnetic resonance imaging (MRI). Methods: Twenty patients with cleft-lip/palate, were clinically evaluated by RDC/TMD and by MRI. The ID of TMJ evaluate were disc displacement with reduction (DDWR) and disc displacement without reduction (DDWOR). Results: The present study showed that 9 (45%) of the patients were diagnosed with ID of TMJ (8 [40%] patients with DDWR and 1 [5%] with DDWOR) and 11 (55%) present no disorders, by RDC/TMD. MRI examination revealed that 15 (75%) of the patients had ID of TMJ (13 [65%] patients with DDWR and 2 [10%] with DDWOR) and 5 (25%) present no disorders.  The Kappa index between the clinical and imaging diagnosis was 0.01. Conclusion: In the present study, DDWR was diagnosed in 40-65% by the RDC/TMD and MRI, respectively; DDWOR was diagnosed in 5-10% by the RDC/TMD and MRI, respectively. The diagnostic correlation between the clinical examination based on RDC and on MRI was weak.